1991
DOI: 10.1111/j.1432-1033.1991.tb15955.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal selectivity of clusters in rabbit liver metallothionein

Abstract: In mammalian metallothioneins the metals are organized in two adamantane-type clusters with three and four metal ions which are tetrahedrally coordinated by thiolate ligands. The metal selectivity of the metal-thiolate clusters in rabbit liver metallothionein has been studied by offering two ions, i. e. Co(II)/Cd(II), Zn(II)/Cd(II) or Co(II)/Zn(II), to the metal-free protein. The heterogeneous metal complexes thus formed were characterized by electronic absorption, magnetic circular dichroism, 'I3Cd-NMR and EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…This can be related to NMR data for the rabbit Cd 4 Zn 3 -MT, which revealed a non-uniform distribution of both metals, 68 and electrochemical studies that revealed several forms of human MT in solution depending on Cd 2+ and Zn 2+ concentration. 22 At moderate Cd 2+ load, the calculations reveal a mixture of many isomers.…”
Section: Compositions Of Cluster a + B Together In Equilibriummentioning
confidence: 55%
See 2 more Smart Citations
“…This can be related to NMR data for the rabbit Cd 4 Zn 3 -MT, which revealed a non-uniform distribution of both metals, 68 and electrochemical studies that revealed several forms of human MT in solution depending on Cd 2+ and Zn 2+ concentration. 22 At moderate Cd 2+ load, the calculations reveal a mixture of many isomers.…”
Section: Compositions Of Cluster a + B Together In Equilibriummentioning
confidence: 55%
“…Thus, no clusterspecific strain is apparent from the metal-ligand bond lengths; (5) for each stoichiometry of Zn 2+ and Cd 2+ , all possible isomers have been characterized and ranked according to relative free energy and the most stable identified; (6) no correlation between stability and angular structural distortion of the sites is observed; (7) specific sites display substantial metal ion selectivity: site 380 in cluster A selectively prefers Cd 2+ , with other sites being more or less neutral to Zn 2+ /Cd 2+ differentiation. In cluster B, site 378 has larger selectivity for Cd 2+ , and 376 has larger selectivity for Zn 2+ ; (8) the most stable distribution in clusters at low Cd 2+ concentration is computed to be Zn 4 68 We have identified which individual isomers occur. The driving force for this preference is enthalpic and can be explained from electrostatic consideration of the thiolate positions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the native Zn(I1) metal ions have been replaced with the paramagnetic Co(I1) ions with the aim to learn more about the structure of the zinc protein. Indeed, Co(I1) is an excellent biochemical probe for Zn(1I) [28]; upon Co(I1) to Zn(I1) replacement, only minor changes (= 5%) in cluster volume are to be expected [29].…”
mentioning
confidence: 99%
“…in order to probe for metal selectivity of MT, we have spectroscopically characterized the cluster forms generated upon binding of various combinations of two different divalent metal ions to metalfree metallothionein, i.e. Co(II), Cd(II), Zn(I1) and Fe(I1) [19]. These studies revealed that homometallic cluster occupation occurs in the case of various ratios of Co/Cd-MT and Fe/Cd-MT.…”
mentioning
confidence: 99%